Pengaruh Kualitas Pelayanan dan Kualitas Produk Terhadap Kepuasan Pengguna Layanan Hak Tanggungan Elektronik (HT-el) - Angela Maria Noni; Azhar Azhar; Raniasa Putra (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
This study aims to determine the effect of service quality and product quality on user satisfaction of electronic mortgage service (HT-el) users at the Land Office of Ogan Komering Ulu Regency. In order to approach this problem, Kotler and Keller's theoretical reference is used, where customer satisfaction is a comparison of service quality and product quality which is expected by customers with what they receive. Meanwhile, the operational theory uses the E-GovQual model by Papadomichelaki and Mentzas, and the product quality model by Kotler and Armstrong. The data were collected through the distribution of questionnaires and analyzed quantitatively. This study concludes that service quality affects the satisfaction of HT-el service users by 48.7 percent, product quality affects the satisfaction of HT-el service users by 63.3 percent, henceforth service quality and product quality simultaneously have a positive and significant effect of 66.1 percent. For this reason, it is necessary to improve the quality of electronic mortgage (HT-el) services, especially on the support capacity (citizen support) involving HT-el implementers. It is recommended to the Land Office to enforce some activities which are related with improving the technical skills and developing the character of HT-el implementers, that is employees of the Land Office of Ogan Komering Ulu.